2004
DOI: 10.1177/0363546503261137
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of the Pectoralis Major Muscle

Abstract: Early surgical treatment by anatomic repair gives the best results in the treatment of total and near-total ruptures of the pectoralis major muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
195
0
19

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(223 citation statements)
references
References 30 publications
5
195
0
19
Order By: Relevance
“…15,16 Although conservative management has been noted to be appropriate in a subset of patients with pectoralis major ruptures, operative treatment is indicated in all young, active patients, regardless of the chronicity of the injury. 1,15,17 Bak et al 15 performed a meta-analysis of 112 cases and reported excellent results in 88% of surgically treated patients with ruptures, compared excellent result in only 27% of patients with ruptures treated nonoperatively. Regardless of significantly better outcomes stemming from operative treatment, a case-by-case approach should be undertaken for each patient presenting with a pectoralis major rupture during treatment decision making.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 Although conservative management has been noted to be appropriate in a subset of patients with pectoralis major ruptures, operative treatment is indicated in all young, active patients, regardless of the chronicity of the injury. 1,15,17 Bak et al 15 performed a meta-analysis of 112 cases and reported excellent results in 88% of surgically treated patients with ruptures, compared excellent result in only 27% of patients with ruptures treated nonoperatively. Regardless of significantly better outcomes stemming from operative treatment, a case-by-case approach should be undertaken for each patient presenting with a pectoralis major rupture during treatment decision making.…”
Section: Discussionmentioning
confidence: 99%
“…At the insertion site on the humeral shaft, the muscle displays a triangular shape. 1,2 The fibers of the diverging layers of tendon, which make up each individual head, twist from their respective origins before coalescing at the insertion site on the humerus. [2][3][4][5][6] Although the main function of the muscle is adduction, the pectoralis major is also responsible for internal rotation, extension, and forward flexion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only approximately 200 cases have been reported in the English literature [1,2]. The pectoralis major is a broad, thick and fan-shaped muscle, originating from the anterior surface of the medial end of the clavicle, the lateral half of the sternum as low down as the cartilaginous attachments of the sixth or seventh rib, the cartilages of all true ribs (with the exception, frequently, of the first or seventh), and from the aponeurosis of the obliquus externus abdominis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the distinction between a partial or complete rupture is of great importance for deciding optimal management. While conservative therapy is justified for partial ruptures [6,13], early surgical management is recommended for a complete rupture [1,2]. Additional investigations like roentgenography and ultrasonography can be helpful, but are usually inconclusive in determining the extent and site of injury.…”
Section: Discussionmentioning
confidence: 99%